Isolated Adrenocorticotropin Deficiency Associated with Delirium and Takotsubo Cardiomyopathy - Masanori Murakami; Noriko Matsushita; Rie Arai; Naohiro Takahashi; Ryuki Kawamura; Sayaka Suzuki; Sachio Takekawa; Fumiko Iwashima; Takashi Shibui; Akihiro Hata; Yoshihiro Ogawa; Toshiyuki Horiuchi (Case Reports in Endocrinology)
We report a 65-year-old woman with isolated adrenocorticotropic hormone (ACTH) deficiency. The patient was transported to the emergency outpatient department by ambulance complaining of malaise and nausea. Because her laboratory data revealed hyponatremia, we performed endocrinological examinations and diagnosed isolated ACTH deficiency. After admission, she went into a delirious state and suffered from takotsubo cardiomyopathy due to adrenal insufficiency. Replacement therapy with hydrocortisone sufficiently improved her delirium and cardiomyopathy. We conclude that her unstable mental state and myocardial dysfunction were closely related to adrenal insufficiency and suggest that adrenal crisis may cause delirium and Takotsubo cardiomyopathy.